Smock Jepang pada Busana Exotic Dramatic Style - Pahreza, Yusuf; Rahmat, Fadri; Rahmanita, Nofi; Yanuarmi, Dini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This article is entitled " Japanese Smock Sewing Decorative Techniques on Exotic Dramatic Style Clothing". The creation of this work was inspired by an exotic dramatic style that displays a more expressive impression and elevates elements of local culture and wisdom. The artist embodies this concept into clothing by using Lurik Woven Fabric and Silungkang Songket combined with Satin material. The clothing created consists of three levels of clothing, namely Ready to Wear, Ready to Wear Deluxe, and Haute Couture. In the creation of this work, the artist uses the Japanese smock technique which will produce a raised texture in the form of waves arranged regularly to create decorative flowers. The choice of the Japanese smock technique is also based on the artist's experience in learning the technique through fabric manipulation during college so that the artist understands the character and visual potential that will be produced. The materials used in the creation of the work are Donatello satin fabric, Lurik woven fabric, Silungkang songket. The creation method starts from searching for sources of ideas and references, making designs, selecting materials, to changing the work. The results of the work show that the application of Japanese smocking techniques to Exotic Dramatic Style clothing is able to produce a unique clothing appearance through the Fabric Manipulation Technique.